Virtual Court Communication Implementation: Studies on the Implementation of Online Criminal Trials in Courts - Widodo, Aan; Pribadi, Slamet; Nurhaliza, Wa Ode Sitti; Akbar, Moh. Rifaldi (Faculty of Law, Universitas Pekalongan, 2024)
Communication in law enforcement that was previously conducted face-to-face is now transformed into electronic-based trials through the support of technology and the internet. Various problems arose during this trial process, specifically regarding infrastructure support, digital literacy, and user technology which are still unequal. This study aims to describe Virtual Trials in Courts from a communication perspective through queries on: (1) how virtual trials are carried out in court, and (2) what are the law enforcement’s challenges in implementing online trials in the Bekasi regency. Researchers conducted interviews with 6 informants, carried out online data searches, and made observations. The results of this study show that the implementation of virtual trials at the Bekasi Regency District Court is a form of supporting an affordable, fast, and simple justice system for the community through media conferences. For the law enforcers, virtual trials have advantages and disadvantages in implementation. The advantages of virtual trials are a form of innovation in the justice system that allows the parties involved in trials without having to be physically present in the courtroom, so there is no need for additional costs. While the weaknesses of virtual trials are related to (1) the validity of examining material or evidence in court, which could not be conducted directly, and(2) the inability of thorough information interpretation due to network constraints. Trial implementation has several limitations as challenges to effective trial implementation, including technology and infrastructure limitations, accessibility limitations, limited interaction between the parties involved, data security limitations, and limited supervision.